Brazilian scientific production in business Administration in the period 2000 - Bertero, Carlos Osmar; Vasconcelos, Flávio Carvalho de; Binder, Marcelo Pereira; Wood Júnior, Thomaz (RAE - Revista de Administracao de Empresas, 2013)
Presentation of the forum: scientific production in Business Administration in the period 2000-2010 with reflections and ideas in the area.